2007
DOI: 10.1007/s10067-006-0508-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary function and bicycle ergometry tests in patients with Behçet’s disease

Abstract: Behçet's disease (BD) has well-defined pulmonary complications, but cardiopulmonary exercise testing and the strength of the respiratory muscles have not been studied in detail. We aimed to investigate the pulmonary functions tests, inspiratory and expiratory muscle strength and endurance, cardiopulmonary exercise test response, and the relationship of these parameters in patients with BD. Forty BD patients and 20 healthy control subjects were recruited for this study. Mean age was 32.95 +/- 7.66 years for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The dynamic factors of pulmonary function depend on different variables such as age, physical activity level, environments pollutants, body composition and prolong disease of the lunges (Prajapati 2008, Game 2006, Wetter 2001, Faintuch 2004, Gökoğlu 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic factors of pulmonary function depend on different variables such as age, physical activity level, environments pollutants, body composition and prolong disease of the lunges (Prajapati 2008, Game 2006, Wetter 2001, Faintuch 2004, Gökoğlu 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is contended that, like metabolic requirements, mechanical limitations of ventilatory muscles are reached only in highly fit athletes [9], and during intensive training, athletes encounter a decline in PaO2 due to decreased transit time of red blood cells through the pulmonary arterials (Gökoğlu 2007, Martin et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation occurs in vascular structures, especially affecting the vascular wall, and related thrombophlebitis and arterial occlusions can be seen 16,17 . In addition, small airway inflammation, fibrosis, and obstructions are the changes seen in the pathophysiological process of Behçet's disease 18,19 . These changes are pathophysiological processes that can cause parenchymal volume loss.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In addition, small airway inflammation, fibrosis, and obstructions are the changes seen in the pathophysiological process of Behçet's disease. 18,19 These changes are pathophysiological processes that can cause parenchymal volume loss. These data prove to us that changes related to vascular involvement in the lung and interstitial involvement that may develop secondary to this process begin at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…35 Gökoglu et al showed that aerobic and respiratory exercises increased the respiratory muscle strength and endurance, aerobic capacity and maximal ventilator capacity in Behçet's patients. 36 In patients with Behçet's disease, CVS involvement is rare, but may occur in different characteristics and may be mortal. Silent myocardial ischemia is also common in these patients and patients who have been diagnosed for more than 10 years are recommended myocardial perfusion scintigraphy.…”
Section: Discussionmentioning
confidence: 99%